Building a Cyber Security Emergency Response Team (CERT) for the NREN Community – The Case of KENET CERT - Muia, Peter; Kashorda, Meoli; Aseda, Kennedy; Osure, Ronald; Njau, Martin (My University, 2015)
Kenya through the regulator, Communications Authority (CA) has setup a national Cyber Security Emergency Response Team (KE-CIRT). This national CERT in Kenya has several sector CERTs with the Kenya Education Network (KENET) having the mandate of setting up and running the education sector CERT in Kenya (Communications Authority of Kenya, 2015). The purpose of the KENET CERT is to identify threats in the Internet and communicate the same to its community (Kenya Education Network CERT, 2015). It also identifies threats within the community and communicates the same to the rest of the Internet community. Additionally, it provides a mechanism where security incidents can be reported and resolved within the KENET community. Experiences are shared with the community and documented for future reference. The CERT is also responsible for making sure that KENET systems and network are safe from security threats. KENET setup the KENET CERT that is run and operated at KENET by the KENET team. This paper and conference session describes the setup of the KENET CERT, the model of operation and the impact and experiences learned from running an NREN CERT in Kenya.
Keywords: Kenya Education Network; Cyber Security Emergency Response Team; Security; National Research and Education Network